The Impact of Corporate Funding Policies on Firm Value: A Comparative Study of Debt, Profit, and Free Cash Flow in Transportation and Logistics Companies - Hadyan, Deni; P Sitorus, Alvin David; Arifin (Management Analysis Journal, 2025)
This study addressed the critical role of Indonesia's transportation and logistics sector in national economic growth, which faced significant pressure from COVID-19 impacts (15.04% decline) and state expenditure cuts (IDR 306.7 trillion). Prior research revealed inconsistent findings on how funding policies affect company value, highlighting a key knowledge gap. The study examined the comparative impact of company debt, profit, and free cash flow on firm value within this sector. Using quantitative methods, financial data from 19 Indonesian-listed transportation/logistics companies (2018–2023, n = 104 observations) were analyzed via multiple linear regression. Results indicated that debt significantly reduced firm value (β = -0.166, p = 0.006), while profit (β = 0.172, p = 0.042) and free cash flow (β = 0.042, p = 0.009) increased it. These findings suggest that optimizing profit retention and cash flow management, while minimizing excessive debt, enhances company resilience and investor appeal.